Penerapan Customer Relations Melalui Akun @Smvapeindonesiagroup Pada Sm Vape Store Indonesia Dalam Mempertahankan Loyalitas Pelanggan - Aliffian Dewantara Wibowo; Rini Ganefwati; Julyanto Ekantoro (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
Vapor technology emerged and invaded the conventional smoking lifestyle, especially among young people. The high level of competition in the retail vape sales business triggers business actors to make various innovations in order to maintain their business. This study examines the application of customer relations strategies through the @smvapeindonesiagroup account at SM Vape Store Indonesia to maintain customer loyalty. The purpose of this study is to determine the costumer relations strategy through the @smvapeindonesiagroup account at SM Vape Store Indonesia to maintain customer loyalty. This research uses descriptive qualitative methods, data collection techniques using observation, interviews, and documentation methods. The primary data source in this research is Ady Yudha Kurniawan as Person In-charge (PIC) of SM Vape Store Indonesia. The results of this study indicate that the customer relations strategy through the @smvapeindonesiagroup account at SM Vape Store Indonesia to maintain customer loyalty has been carried out optimally, by utilizing the IDIC method, the method is identify, differentiate, interact, and customize which makes SM Vape Store Indonesia have many loyal customers.